Blood, saliva and urine maresin-1 and malondialdehyde may be useful biomarker in patients with polycystic ovary syndrome: a prospective study - Yavuz, Adem; Ugur, Kader; Karagoz, Zuhal Karaca; Ayan, Durmus; Aydin, Suleyman (Imr Press, 2022)
Background: Maresin-1 (MaR1) plays a major role in many inflammatory disorders. Polycystic ovary syndrome (PCOS) aside from a hormonal disorder, an inflammation might also contribute to PCOS and its metabolic associations. Therefore, the purpose of this prospective study first time was to find out the blood, saliva and urine levels of MaR1 in PCOS patients and evaluate the correlations with other metabolic and hormonal parameters. Methods: Thirty PCOS patients and 30 matched healthy controls were enrolled to prospective case control study. Blood, urine and saliva samples were simultaneously collected from participants after overnight fasting. MaR1 levels in blood, urine and saliva samples were determined by enzyme-linked immunosorbent assay. Ferriman-Gallwey score, anthropometric, hormonal and some other metabolic parameters were also recorded. Regression analysis was preformed to find out the relationship between MaRI, C-reactive protein (CRP) and malondialdehyde (MDA), and hormonal and metabolic parameters. Results: Patients with PCOS compared with control women had higher MDA and CRP and decreased MaR1 levels. Blood, urine and saliva MDA and MaR1 levels were similar and indicated parallel decrease or increase in the PCOS and control groups. Furthermore, regression analysis indicated that blood CRP and MDA was positively associated with luteinizing hormone (LIT) and fasting insulin (H) in PCOS group (p < 0.05) while blood, urine and saliva MaR1 was negatively associated with CRP and MDA. Conclusions: Present results (MaR1, CRP and MI)A together) in case of PCOS suggests that decreased MaR1 and elevated MDA and CRP levels in patients with PCOS and may be considered as a useful early biomarker (especially MaR1) in diagnosis of PCOS disease that has not been previously reported and regular monitoring of their levels could be helpful in clinical decisions.
Keywords: urine; saliva; maresin-1; malondialdehyde; polycystic ovary syndrome